Aluminum-plated steel plate for hot stamping

By adding needle-like compounds of specific structures to the surface treatment film of the aluminum-plated steel plate, the heating speed of the aluminum-plated steel plate is improved, and the problem of low heating efficiency of aluminum-plated steel plates in the prior art is solved, and more efficient hot stamping members are realized Production.

CN119301304APending Publication Date: 2025-01-10NIPPON STEEL CORPORATION
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380043998.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-14
Filing Date
2023-07-14
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing hot stamping method and aluminum-plated steel plates have low productivity during the heating process, especially because the film of the steel plate contains organic matter such as carbon pigment disappears at high temperatures, resulting in low heating efficiency of aluminum-plated steel plates.

Method used

The surface treatment film of the aluminum-plated steel plate is added with a hexagonal crystalline needle-like compound with a ratio of 4 or more to a short diameter of 50 or less, and the needle-like compound is at an angle of 0 degrees or more to the surface of the aluminum plating layer and Needle-shaped compound below 40 degrees to increase heating speed.

Benefits of technology

By increasing the heating speed of the aluminum-plated steel plate, the productivity of the hot stamping member is significantly improved, the heating time is reduced, and the mechanical strength and shape fixability of the finished product are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119301304A_ABST
    Figure CN119301304A_ABST
Patent Text Reader

Abstract

This aluminum-plated steel sheet for hot stamping has a base steel sheet, an aluminum plating layer provided on at least one surface of the base steel sheet, and a surface-treated coating film provided on the aluminum plating layer, the surface-treated coating film containing a needle-like compound X, the ratio of the major axis to the minor axis is 4-50, and the ratio of needle-like compounds X1 having a hexagonal crystal structure is 70% or more by number%. The ratio of the needle-like compound X2 in which the smaller angle is 0-40 degrees (inclusive) among the angles at the intersection of a straight line parallel to the major axis and a straight line parallel to the surface of the aluminum plating layer is 70% or more by number%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an aluminum-plated steel sheet for hot stamping.

[0002] This application claims priority based on Japanese Patent Application No. 2022-113179 filed in Japan on July 14, 2022, the contents of which are incorporated herein by reference. Background Art

[0003] In recent years, in order to protect the environment and prevent global warming, the demand for suppressing the consumption of chemical fuels has increased, and this demand has had an impact on various manufacturing industries. For example, automobiles, which are indispensable as a means of transportation in daily life or activities, are no exception, and there is a demand for improved fuel efficiency by reducing the weight of the vehicle body, etc. However, with regard to automobiles, simply reducing the weight of the vehicle body may reduce safety, so it is not preferred in terms of product quality.

[0004] Therefore, when reducing the weight of a vehicle body, it is necessary to appropriately implement it while ensuring safety.

[0005] Most of the structure of a car is formed by iron, especially steel plates. Therefore, reducing the weight of the steel plates is effective for lightweighting the car body. In addition, such a demand for reducing the weight of steel plates is not only carried out in the automobile manufacturing industry, but also in various manufacturing industries. In response to such a demand, if the weight of the steel plate is simply reduced, it is considered to reduce the thickness of the steel plate. However, reducing the thickness of the steel plate will cause a decrease in the strength of the structure. Therefore, in recent years, research and development has been carried out on steel plates that can maintain or improve the mechanical strength of structures composed of steel plates even if they are thinner than the previous steel plates used before by improving the mechanical strength of the steel plates.

[0006] Generally speaking, materials with high mechanical strength tend to have reduced shape fixity during forming processes such as bending. Therefore, when materials with high mechanical strength are processed into complex shapes, the processing itself becomes difficult. As one of the means for solving such problems regarding formability, the so-called "hot stamping method (also called hot pressing method, hot pressing method, high temperature pressing method or die quenching method)" can be cited.

[0007] In the hot stamping method, the material to be formed is heated to a high temperature and transformed (austenized) into a structure called austenite, and the steel plate softened by heating is pressed to form, and then cooled after forming. According to the hot stamping method, since the material is temporarily heated to a high temperature and softened, the material can be easily pressed. Furthermore, the mechanical strength of the material can be improved by the quenching effect brought about by cooling after forming. Therefore, by the hot stamping method, a formed product with good shape fixity and high mechanical strength can be obtained.

[0008] For example, Patent Document 1 discloses a technique for manufacturing a formed product that can be used as an automobile component by processing an alloyed hot-dip galvanized steel sheet by a hot stamping method.

[0009] Patent Documents 2 and 3 disclose a technique for providing an aluminum-plated steel sheet with a film mainly composed of an organic substance such as a carbon pigment, thereby accelerating the time required for heating to a desired temperature.

[0010] Prior art literature

[0011] Patent Literature

[0012] Patent Document 1: Japanese Patent Application Publication No. 2003-126921

[0013] Patent Document 2: Japanese Patent Application Publication No. 2011-149084

[0014] Patent Document 3: Japanese Patent Application No. 2017-518438 Summary of the invention

[0015] Problems to be solved by the invention

[0016] Among them, the hot stamping method described in Patent Document 1 requires heating the steel sheet to be processed to 700 to 1000° C. Therefore, time must be ensured for heating the steel sheet to a desired temperature, and improvement in productivity is not sufficient.

[0017] In addition, regarding the aluminum-plated steel sheets described in Patent Documents 2 and 3, since the carbon pigments and the like contained in the film on the steel sheets are all organic substances, when the aluminum-plated steel sheets are heated to a high temperature region of 750° C. or higher, these organic substances disappear. Therefore, regarding the technologies described in Patent Documents 2 and 3, the improvement in productivity is also insufficient.

[0018] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide an aluminum-plated steel sheet for hot stamping that can further improve the productivity of hot stamped parts.

[0019] Means for solving problems

[0020] In order to solve the above-mentioned problems, the inventors have conducted in-depth research. As a result, it was found that when hot stamping aluminum-plated steel sheets are used to manufacture hot stamping components, if the heating rate when the steel sheet is heated to the desired temperature (for example, above the Ac3 point) can be increased, the heating time can be shortened, which can help improve productivity. Specifically, it was found that by including 70% of the needle-shaped compounds X1 having a ratio of the long diameter to the short diameter of 4 or more and 50 or less and having a hexagonal crystal structure in the surface treatment film provided on the coating, and in the needle-shaped compound X1, more than 70% of the needle-shaped compounds X2 having the smallest angle between the straight line parallel to the long diameter and the surface of the above-mentioned aluminum coating being 0 degrees or more and 40 degrees or less, the heating rate is greatly increased, and as a result, productivity can be improved.

[0021] The gist of the present invention accomplished based on the above findings is as follows.

[0022] [1] An aluminum-plated steel sheet for hot stamping according to one embodiment of the present invention is an aluminum-plated steel sheet for hot stamping comprising a base steel sheet, an aluminum coating provided on at least one surface of the base steel sheet, and a surface treatment film provided on the aluminum coating, wherein the surface treatment film contains a needle-shaped compound X, wherein among the needle-shaped compounds X, the proportion of needle-shaped compounds X1 having a hexagonal crystal structure and having a ratio of a major axis to a minor axis of 4 or more and 50 or less is 70% or more in terms of number %, and among the needle-shaped compounds X1, the proportion of needle-shaped compounds X2 having a minimum angle of 0 degrees or more and 40 degrees or less among the angles formed between a straight line parallel to the major axis and the surface of the aluminum coating is 70% or more in terms of number %.

[0023] [2] In the aluminum-plated steel sheet for hot stamping according to [1] above, the content R of the needle-shaped compound X1 may be 2% to 60% by volume.

[0024] [3] In the aluminum-plated steel sheet for hot stamping according to [1] or [2] above, the carbon concentration of the needle-shaped compound X1 may be 90% by mass or more.

[0025] [4] According to any one of the above [1] to [3], in the aluminum-plated steel sheet for hot stamping, when the content R of the needle-shaped compound X1 is measured at 10 locations and the maximum content is set to R1 and the minimum content is set to R2, the ratio R1 / R2 of R1 to R2 can also be less than 2.0.

[0026] [5] The aluminum-plated steel sheet for hot stamping according to any one of [1] to [4], wherein the needle-shaped compound X1 may be graphite.

[0027] [6] The aluminum-plated steel sheet for hot stamping according to any one of [1] to [5], wherein the surface treatment film may contain a resin.

[0028] Effects of the Invention

[0029] According to the above aspect of the present invention, it is possible to provide a hot stamping steel sheet capable of further improving the productivity of a hot stamped component. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a schematic cross-sectional view of an aluminum-plated steel sheet for hot stamping according to one embodiment of the present invention.

[0031] Figure 2 This is a diagram showing the short axis and long axis of a needle-shaped compound.

[0032] Figure 3 It is a schematic cross-sectional view of an aluminum-plated steel sheet for hot stamping according to one embodiment of the present invention.

[0033] Figure 4 It is a schematic cross-sectional view of an aluminum-plated steel sheet for hot stamping according to one embodiment of the present invention. DETAILED DESCRIPTION

[0034] Hereinafter, a preferred embodiment of the present invention will be described in detail. It should be noted that the present invention is not limited to the configuration disclosed in the present embodiment, and various changes can be made without departing from the gist of the present invention. In addition, for the following numerical ranges, the lower limit and the upper limit are included in the range. Regarding the numerical value expressed as "exceeding" or "lower than", the value is not included in the numerical range. The "%" about the content of each element refers to "mass %".

[0035] (Aluminum-plated steel sheet for hot stamping)

[0036] When the aluminum-plated steel sheet for hot stamping (hereinafter, also referred to as "aluminum-plated steel sheet for HS") according to an embodiment of the present invention is used to manufacture a hot stamping component, the heating rate when the aluminum-plated steel sheet for HS is heated can be increased. That is, by using the aluminum-plated steel sheet for HS according to the embodiment of the present invention that can increase the heating rate during heating, the productivity of the hot stamping component can be improved.

[0037] In order to improve the heating rate when heating the aluminum-plated steel sheet for HS, the aluminum-plated steel sheet for hot stamping of the present embodiment has a surface treatment film containing a needle-shaped compound on at least one surface of the plated steel sheet with an aluminum coating. In the present embodiment, by imparting a surface treatment film containing a prescribed needle-shaped compound described later to at least one surface of the plated steel sheet with an aluminum coating as described above, the heating rate of the obtained aluminum-plated steel sheet for HS when heated can be accelerated. It should be noted that the surface treatment film can be formed on both sides of the plated steel sheet with an aluminum coating, or it can be only one surface. In addition, the surface treatment film can be formed on the entire surface of the plated steel sheet with an aluminum coating, or it can be a part of the surface, but from the viewpoint of further improving the productivity of the hot stamping component, the surface treatment film is preferably provided on the entire surface of the plated steel sheet with an aluminum coating.

[0038] In the hot stamping aluminum-plated steel sheet of the present embodiment, the type of steel sheet (parent steel sheet) that becomes the base material is not particularly limited. As the parent steel sheet, for example, various hot-rolled steel sheets and cold-rolled steel sheets can be listed. The plated steel sheet constituting the hot stamping aluminum-plated steel sheet of the present embodiment is a steel sheet having a coating on at least one surface of such a parent steel sheet. As the plated steel sheet, for example, a steel sheet that has been subjected to hot-dip aluminum plating can be listed. However, as long as it can be applied to hot stamping, the coating of the present embodiment is not limited to the hot-dip aluminum coating layer.

[0039] Conventionally, most of the steel sheets used for automobile frame parts are hot-rolled steel sheets, cold-rolled steel sheets, or plated steel sheets plated with aluminum, zinc, etc. These conventional steel sheets have low emissivity, and therefore have a low heating rate with respect to radiation heating.

[0040] In the hot stamping aluminum-plated steel sheet of the present embodiment, by applying a predetermined surface treatment film described later to at least one surface of the coating layer, the heating rate during hot stamping heating can be increased. Specifically, by heating the HS aluminum-plated steel sheet having a predetermined surface treatment film and hot stamping the heated HS aluminum-plated steel sheet, the productivity of the hot stamping component can be further improved.

[0041] <Surface treatment film>

[0042] Figure 1 A schematic cross-sectional view showing a surface portion of one of the surfaces of the aluminum-plated steel sheet for hot stamping according to the present embodiment. Figure 1 The schematic diagram is for explanation. The size or distribution state of the surface treatment film 13, the aluminum plating layer 12 and the needle-shaped inclusions X (X1) does not necessarily represent a preferred embodiment and is not limited to Figure 1The dimensions and dimensional ratios of the base steel sheet, the aluminum plating layer, and the surface treatment film can be arbitrarily designed according to the desired properties of the aluminum-plated steel sheet for hot stamping.

[0043] like Figure 1 As shown in , the aluminum-plated steel sheet 10 for hot stamping of the present embodiment has, for example, a base steel sheet 11, an aluminum coating 12 provided on at least one surface of the base steel sheet 11, and a surface treatment film 13 provided on the aluminum coating 12. The surface treatment film 13 contains a needle-shaped compound X. In the aluminum-plated steel sheet 10 for hot stamping of the present embodiment, the emissivity of the surface on the side to which the surface treatment film 13 is applied (i.e., the surface of the surface treatment film 13) is high. Therefore, the heating rate during hot stamping heating is large, and as a result, the productivity of the hot stamping component can be further improved.

[0044] <<Needle-shaped compounds>>

[0045] The needle-shaped compound X contained in the surface treatment film 13 includes a needle-shaped compound X1 having a hexagonal crystal structure and a ratio of a major axis to a minor axis of 4 or more and 50 or less.

[0046] The surface treatment film 13 of the present embodiment may further contain an adhesive component or various additives as needed. In addition, the surface treatment film 13 of the present embodiment may not contain silicon dioxide, or may contain silicon dioxide within a certain range. Furthermore, in the present embodiment, by adjusting the content of the needle-shaped compound in the surface treatment film 13, the film thickness of the surface treatment film 13, etc., it is possible to achieve an increase in the heating rate during hot stamping heating.

[0047] Hereinafter, constituent elements of the surface treatment film 13 will be described in detail.

[0048] Surface treatment film 13 such as Figure 1As shown in , it is applied above the aluminum plating layer 12 applied to one or both surfaces of the base steel plate 11. The needle-shaped compound X exists in the surface treatment film 13. That is, the surface treatment film 13 contains the needle-shaped compound X. As described below, the proportion of the needle-shaped compound X1 and the proportion of the needle-shaped compound X2 in the surface treatment film 13 are important, and it is not necessary to specify the content (content rate) of the needle-shaped compound X in the surface treatment film 13. However, as required, the content (content rate) of the needle-shaped compound X in the surface treatment film 13 may be 0.5% or more, 1% or more, or 2% or more in volume %, or (when the content of the needle-shaped compound X in the surface treatment film 13 is not specified) the content (content rate) of the needle-shaped compound X1 in the surface treatment film 13 may also be specified. It should be noted that the volume % of the needle-shaped compound X in the surface treatment film 13 can be measured according to the method for measuring the volume % of the needle-shaped compound X1 in the surface treatment film 13 described later.

[0049] The ratio of the major axis to the minor axis of the needle-shaped compound X1 having a hexagonal crystal structure contained in the surface treatment film 13 of the present embodiment is 4 or more and 50 or less. The lower limit of the ratio is preferably 6 or more, more preferably 8 or more. In addition, the upper limit of the ratio is preferably 30 or less, more preferably 20 or less.

[0050] Generally speaking, in crystal structure, the crystal system that crystal is classified according to symmetry has 6 kinds of cubic system, tetragonal system, hexagonal system, orthorhombic system, monoclinic system and triclinic system. About symmetry, cubic system is the highest. Crystal system easily affects the shape of compound, and with respect to the compound of cubic system, because symmetry is high, it is easy to grow isotropically in each axial direction of three-dimensional. On the other hand, with respect to hexagonal system, it is easy to have anisotropy, and needle-shaped compound can be formed. With respect to compounds such as other orthorhombic systems or monoclinic systems, the compound falling into the range of the ratio of the above-mentioned major diameter to the minor diameter is few.

[0051] As for the compound of hexagonal system, the heat absorption from the surrounding is fast. The reason is not clear, but it can be considered that it is due to: as for the compound of hexagonal system, the length of the axis of the unit cell is the same in 3 directions, on the other hand, 2 of the 3 axis angles are 90 degrees, and the remaining 1 is 120 degrees, so it is possible to absorb heat (especially radiant heat) from the surrounding three-dimensionally. On the other hand, as for other crystal systems, since the axis angles are all 90 degrees, it is possible that radiant heat cannot be widely absorbed.

[0052] The needle-shaped compound X1 contained in the surface treatment film 13 of the present embodiment is a hexagonal crystal. However, it is not necessary for all needle-shaped compounds to be hexagonal, and needle-shaped compounds of other crystal systems may be contained. However, from the viewpoint of improving heat absorption, the ratio of the hexagonal needle-shaped compound X1 contained in the film to all needle-shaped compounds (the ratio of the needle-shaped compound X1 to the needle-shaped compound X) is set to 70% or more in terms of number %. All needle-shaped compounds may also be hexagonal.

[0053] If the ratio of the long diameter to the short diameter of the needle-shaped compound X1 is too small, the surface area per unit volume of the needle-shaped compound X1 cannot be sufficiently ensured, and the heat absorption efficiency during heating may become insufficient. As a result, the heating rate when the aluminum-plated steel sheet is heated cannot be sufficiently increased, and sometimes the productivity is poor. In the present embodiment, by setting the ratio of the long diameter to the short diameter of the needle-shaped compound X1 to 4 or more, the surface area per unit volume of the needle-shaped compound X1 becomes larger, and the radiant heat from the heating atmosphere can be efficiently absorbed. As a result, the heating rate of the aluminum-plated steel sheet during hot stamping can be accelerated. On the other hand, if the ratio of the long diameter to the short diameter of the needle-shaped compound X1 is too large, it may hinder the absorption of radiant heat generated by other needle-shaped compounds present in the vicinity of the needle-shaped compound X1. As a result, the heating rate when the aluminum-plated steel sheet is heated cannot be sufficiently increased, and sometimes the productivity is poor. In this embodiment, by setting the ratio of the major axis to the minor axis of the needle-shaped compound X1 to less than 50, the interference with the absorption of radiant heat by other needle-shaped compounds existing nearby can be suppressed, so that heat can be efficiently absorbed in the entire film. As a result, the heating rate of the aluminum-plated steel sheet during hot stamping can be accelerated.

[0054] Here, the crystal system and the ratio of the major axis to the minor axis of the needle-shaped compound X in the surface treatment film 13 can be measured by cross-sectional analysis of the surface treatment film using a transmission electron microscope (TEM), energy dispersive X-ray spectroscopy (EDS) and electron beam diffraction.

[0055] Specifically, the cross section of the membrane is used as the observation surface, and the needle-shaped compound X is selected from the TEM image obtained by observing the TEM observation sample of the membrane thickness × 50μm × (thickness of the sample) about 100nm. From the electron beam diffraction image of the needle-shaped compound X, the crystal structure such as the hexagonal system can be determined. It should be noted that the TEM observation sample is made by FIB processing using a focused ion beam device ("FIB NB 5000" made by Hitachi High-Technologies). The acceleration voltage during processing is set to 40kV. In addition, the observation surface is set to a cross section perpendicular to the rolling direction of the steel plate (the so-called C cross section), and the observation position is adjusted in a manner orthogonal to the above cross section during observation.

[0056] Here, the "needle-shaped compound X" in the present embodiment refers to a compound that grows relatively large only in one direction, and a continuous compound whose carbon concentration ratio falls within ±5% by mass in EDS analysis is regarded as one compound, and a compound whose ratio of the long diameter to the short diameter in the ratio of the short diameter to the long diameter of the compound is 2 or more is set as the needle-shaped compound X. By containing a needle-shaped compound X1 in which the ratio of the long diameter to the short diameter in the needle-shaped compound X is 4 or more and 50 or less in the film, the heating rate of the aluminum-plated steel sheet for hot stamping can be increased.

[0057] The short and long diameters can be Figure 2 It is obtained by the following steps as shown in .

[0058] First, in the TEM image of the needle-shaped compound X, a continuous compound having a contrast different from that of the surroundings and a C concentration falling within ±5 mass % in the EDS analysis was determined to be one needle-shaped compound X. Figure 2 The rectangle with the smallest area among the rectangles circumscribing the particle shown in (a) to (c) is the rectangle with the smallest area (in Figure 2 In the case of (a), the shorter side and the longer side in (a) are defined as the short diameter and the long diameter, respectively. It should be noted that, for example, a needle-shaped compound having a C concentration in the range of 0 to 10 mass % satisfies the above-mentioned necessary conditions for C concentration, and therefore a compound having a different contrast from the surrounding and continuous in the TEM image is determined as one needle-shaped compound X.

[0059] In addition, in the surface treatment film 13 of the present embodiment, the ratio of the major axis to the minor axis is 4 or more and 50 or less, and the ratio of the needle-shaped compound X2 (the ratio of the needle-shaped compound X2 to the needle-shaped compound X1) in the hexagonal system needle-shaped compound X1, in which the smallest angle α formed by the straight line parallel to the major axis and the surface of the coating 12 is 0 degrees or more and 40 degrees or less, is 70% or more in terms of number %. If the smallest angle α formed by the straight line parallel to the major axis of the needle-shaped compound X1 and the coating surface exceeds 40 degrees, the absorption of radiant heat is insufficient and the heating rate does not increase. It is presumed that this is because: when the angle α exceeds 40 degrees, electromagnetic waves represented by infrared light are not absorbed by the needle-shaped compound X1 and reach the aluminum coating layer with low emissivity and are reflected. Therefore, in order to increase the heating rate of the aluminum-plated steel sheet for HS, it is effective to fully increase the ratio of the needle-shaped compound X2 in the needle-shaped compound X1 in which the angle α is 0 degrees or more and 40 degrees or less. The ratio of the needle-shaped compound X2 may also be 100% (i.e., the angle α of all needle-shaped compounds X1 is greater than or equal to 0 degrees and less than or equal to 40 degrees). It should be noted that the angle α in this embodiment can be measured from a TEM image obtained by observing the above-mentioned TEM observation sample (film thickness × 50 μm × (sample thickness) about 100 nm).

[0060] It should be noted that the so-called smallest angle α among the angles formed by a straight line parallel to the long axis of the needle-shaped compound X1 and the plated surface, when the straight line parallel to the long axis of the needle-shaped compound X1 is defined as straight line A, can refer to the smaller angle among the angles formed by the intersection B of the above-mentioned surface Z and the plated surface and the above-mentioned straight line A within the surface Z that is perpendicular to the plated surface and contains the straight line A.

[0061] The ratio of the needle-shaped compound X1 is determined by the following method.

[0062] By using the above-mentioned method of TEM observation sample (film thickness × 50 μm × (thickness of sample) about 100 nm), 10 arbitrary needle-shaped compounds X are selected from the compounds determined to be needle-shaped compounds X, and the number ratio (number %) of needle-shaped compounds X1 having a ratio of the long diameter to the short diameter of 4 or more and 50 or less and having a hexagonal crystal structure among these 10 compounds is calculated. Specifically, 10 compounds are randomly selected from the compounds determined to be needle-shaped compounds X, and if there are 7 needle-shaped compounds X1 having a ratio of the long diameter to the short diameter of 4 or more and 50 or less and having a hexagonal crystal structure among these 10 compounds, the ratio of needle-shaped compounds X1 in this area is set to 70%. Such measurement is repeated 10 times, and by averaging the obtained ratios of needle-shaped compounds X1, the ratio (number %) of needle-shaped compounds X1 in the surface treatment film 13 is calculated.

[0063] The ratio of the needle-shaped compound X2 is determined by the following method.

[0064] By using the above-mentioned method of the TEM observation sample (film thickness × 50 μm × thickness 100 nm), 40 needle-shaped compounds X1 are randomly selected from the compounds determined to be needle-shaped compounds X1, and the number ratio (number %) of needle-shaped compounds X2 whose angle α satisfies 0 degrees or more and 40 degrees or less is calculated. Specifically, 40 are randomly selected from the compounds determined to be needle-shaped compounds X, and if there are 30 needle-shaped compounds X2 whose angle α satisfies 0 degrees or more and 40 degrees or less, the ratio of needle-shaped compounds X2 in this area is set to 75%. By this measurement, the ratio (number %) of needle-shaped compounds X2 in the surface treatment film 13 is calculated.

[0065] Here, the needle-shaped compound X1 contained in the surface treatment film 13 has a hexagonal crystal structure as described above. That is, the needle-shaped compound X1 is not an amorphous compound represented by carbon black, but a crystalline compound. When an amorphous compound is used as the needle-shaped compound X1, the heating rate during hot stamping cannot be sufficiently increased, and it is sometimes difficult to ensure the adhesion of the surface treatment film.

[0066] Examples of the compound having a hexagonal crystal structure include lanthanum silicate, magnesium diboride, beryllia, zinc oxide, graphite (C), β-quartz, nickel ore (NiS), and wurtzite (ZnS).

[0067] The reason why the temperature rise rate during hot stamping is increased by including a compound having a hexagonal crystal structure in the film is not clear, but it is considered that a large number of active bonds exist for infrared rays with a wavelength of 1 to 10 μm, which are particularly effective in absorbing radiant heat.

[0068] like Figure 3 As shown in , a base treatment film 14 may also be provided in the lower layer of the surface treatment film 13 (between the surface treatment film 13 and the aluminum plating layer 12). By doing so, the adhesion of the surface treatment film 13 on the upper layer side to the aluminum plating layer 12 can be improved. In this case, as the base treatment film 14, for example, there is a film containing elements such as carbon, oxygen, hydrogen, nitrogen, silicon, sodium, etc., such as a silane coupling agent, and the upper layer thereof has a surface treatment film 13 containing a needle-shaped compound having a hexagonal crystal structure. It should be noted that Figure 3 The schematic diagram is a simple diagram for explanation. The size or distribution state of the surface treatment film 13, the base treatment film 14, the aluminum plating layer 12 and the needle-shaped inclusions X (X1) does not necessarily represent a preferred embodiment and is not limited to Figure 3 size or distribution.

[0069] In addition, in order to further improve the corrosion resistance of the surface treatment film 13, a film 15 may be provided on the upper layer of the surface treatment film 13. As the film 15, a resin film such as polyester resin or polyurethane resin containing no inorganic components such as silicon or metal or containing a trace amount thereof may be cited. In the case where the film 15 has a resin film, it is preferred that: Figure 4 As shown in , there is a base treatment film 14 on the aluminum plating layer 12, a surface treatment film 13 thereon, and a resin film on the surface treatment film 13. It should be noted that, Figure 4 The diagram is a simple schematic diagram for explanation. The size or distribution state of the film 15, the surface treatment film 13, the base treatment film 14, the aluminum plating layer 12 and the needle-shaped inclusions X (X1) does not necessarily represent a preferred embodiment and is not limited to Figure 4 size or distribution.

[0070] In the surface treatment film 13 of the present embodiment, in addition to the above-mentioned needle-shaped compound, various adhesive components or additives may also be contained. The surface treatment film 13 preferably contains resins and pigments, for example. In the surface treatment film 13, in addition to these components, additives such as leveling agents, defoamers, colorants, viscosity modifiers, and ultraviolet absorbers may also be contained. It should be noted that the coating liquid used to form the surface treatment film 13 is preferably obtained by dispersing or dissolving the above-mentioned components in water or a solvent.

[0071] In this embodiment, specific methods for providing the surface treatment film 13 include painting and lamination, but are not limited to these methods. The surface treatment film 13 may be provided on only one surface of the steel plate or on both surfaces of the steel plate.

[0072] When applying the surface treatment film 13 to the entire surface of the aluminum plating layer 12 by coating, first, for example, an organic or inorganic treatment liquid containing a needle-shaped compound having a hexagonal crystal structure and a ratio of the major axis to the minor axis of 4 or more and 50 or less is prepared. Then, the treatment liquid is applied to the entire surface of the aluminum plating layer 12 by a roll coater, a curtain coater, an inkjet, etc., and the volatile components in the treatment liquid are dried to provide the surface treatment film 13. In particular, coating by inkjet is preferred because the film thickness can be continuously changed.

[0073] Here, in the past (e.g., Patent Document 2, etc.), when organic substances such as carbon pigments are included in the surface treatment film, there is a problem that these organic substances disappear if the plated steel sheet is heated to a high temperature region (e.g., above 750°C). However, the present inventors have found that in the case of the surface treatment film 13 of the present embodiment, it is possible to heat to a high temperature region without causing the disappearance of organic compounds other than the needle-shaped compound X1 having a hexagonal crystal structure. The mechanism by which it is possible to heat to a high temperature region without causing the disappearance of organic substances is not clear, but it is inferred that by optimizing the ratio of the long diameter to the short diameter of the needle-shaped compound contained in the film, the organic substance used as the treatment liquid is changed to a structure that can be tolerated even in a high temperature region.

[0074] The aluminum-plated steel sheet 10 for hot stamping of the present embodiment has the surface treatment film 13 having the above-mentioned characteristics, and can increase the heating rate during hot stamping. Therefore, by using the aluminum-plated steel sheet 10 for hot stamping of the present embodiment as a raw material, the productivity of hot stamping materials can be improved.

[0075] The substance (needle-shaped compound) contained in the surface-treated film 13 which is characteristic in realizing the surface-treated film 13 as described above will be described in more detail below.

[0076] [Content R of needle-shaped compound X1]

[0077] On the side of the surface of the aluminum plating layer 12 to which the surface treatment film 13 is applied, the content R of the needle-shaped compound X1 having a hexagonal crystal structure in the surface treatment film 13 is preferably 0.5% by volume or more or 1% by volume or more. By setting the content R to 1% by volume or more, the heating rate during hot stamping can be sufficiently accelerated. The content R is preferably 2% by volume or more, more preferably 5% by volume or more, and further more preferably 10% by volume or more. The content R is preferably 60% by volume or less. By setting it to 60% by volume or less, the electrical attraction between the adhesive component of the surface treatment film 13 and the surface of the aluminum plating layer 12 as the substrate can be ensured, and the adhesion can be improved. The content R is preferably 40% by volume or less, more preferably 20% by volume or less.

[0078] It should be noted that the content rate R is the volume rate (volume %) of the needle-shaped compound X1 in the surface treatment film 13 in the TEM image, and can be obtained by the following steps. The volume of each needle-shaped compound X1 is calculated from the size of each needle-shaped compound X1 in the TEM observation area (for example, the short axis corresponding to the diameter of the needle-shaped compound X1 and the long axis corresponding to the length of the needle-shaped compound X1), and the total of the volumes is divided by the volume of the observation area (field of view area × thickness) to calculate the volume rate of the needle-shaped compound X1. This measurement is repeated 10 times, and the average of the volume rates of 10 fields of view is taken as the content rate R.

[0079] [Short diameter of needle-shaped compound X1]

[0080] The short diameter of the needle-shaped compound X1 contained in the surface treatment film 13 is preferably 20 nm or more. The thickness of the surface treatment film 13 is sometimes locally different due to the roughness and waviness of the base steel plate, or the difference in the volatilization rate of volatile components such as water in the treatment liquid when the film is formed. In this case, it is preferred that the short diameter of the needle-shaped compound X1 is 20 nm or more, so that the surface treatment film 13 can efficiently absorb radiant heat. The short diameter of the needle-shaped compound X1 is preferably 2 μm or less. By being 2 μm or less, it becomes easy to ensure the contact point between the aluminum-plated steel plate of the substrate and the electrode during welding after hot stamping, which can improve the spot weldability. The short diameter is preferably 30 nm or more, or 60 nm or more, or 1 μm or less, 700 nm or less, or 500 nm or less.

[0081] [Long diameter of needle-shaped compound X1]

[0082] The long diameter of the needle-shaped compound X1 contained in the surface treatment film 13 is preferably 80 nm or more. When the long diameter of the needle-shaped compound X1 is 80 nm or more, it is preferred because the surface treatment film 13 can efficiently absorb radiant heat for the same reason as the above-mentioned short diameter. The long diameter of the needle-shaped compound X1 is preferably 100 μm or less. When the long diameter is 100 μm or less, it is preferred because it becomes easy to ensure the contact point between the aluminum-plated steel sheet of the substrate and the electrode during welding after hot stamping for the same reason as the above-mentioned short diameter, which can improve the spot weldability. The long diameter is preferably 150 nm or more, 300 nm or more, or 50 μm or less, 20 μm or less, or 10 μm or less.

[0083] [Carbon concentration of needle-shaped compound X1]

[0084] The carbon concentration of the needle-shaped compound X1 is more preferably 90% by mass or more. By having a carbon concentration of 90% by mass or more, even if the temperature rises during hot stamping, the disappearance of the needle-shaped compound X1 from the film due to decomposition, etc. can be delayed, and the function of absorbing heat can be maintained even in a high temperature range. Furthermore, if the carbon concentration of the needle-shaped compound X1 is 90% by mass or more, the reaction of the needle-shaped compound X1 with oxygen in the atmosphere becomes an exothermic reaction, so the heating rate can be further accelerated. The carbon concentration is preferably 90% by mass or more. It should be noted that the carbon concentration can be obtained from the measured value of EDS. That is, the spectrum of the characteristic X-rays during electron beam irradiation is measured, and the detection intensity of each energy is calculated. The elements constituting the needle-shaped compound are determined by the energy value, and the concentration of the element can be calculated from the detection intensity. By such a method, the original concentration of carbon, etc. constituting the needle-shaped compound X1 can be analyzed. The carbon concentration of the needle-shaped compound X1 thus obtained is preferably 100% by mass or less. When the carbon concentration is 100 mass % or less, the above-mentioned exothermic reaction proceeds and the effect of further accelerating the temperature rise rate can be expected.

[0085] [Dispersion degree of needle-shaped compound X1]

[0086] When the compound in the surface treatment film is in the form of a needle, the surface area per unit volume of the compound is large. Therefore, when the aluminum-plated steel sheet of the present embodiment is heated to manufacture a hot stamping component, the surface treatment film as a whole can absorb heat efficiently by the radiation generated by the electromagnetic waves from the heated atmosphere. In addition, heat can also be efficiently absorbed by the heat conduction generated by the contact with the heated atmosphere gas. As a result, the entire surface treatment film can be heated rapidly without unevenness. In order to obtain such an effect, it is effective to set the form of the compound in the film to a needle-like shape with a ratio of the major diameter to the minor diameter being greater than 4 and less than 50, and to disperse such a needle-like compound X1 in the entire surface treatment film.

[0087] The dispersion degree of the needle-shaped compound X1 is calculated using the data when the proportion of the needle-shaped compound X1 is measured. Specifically, when the proportion of the needle-shaped compound X1 is measured, the operation of measuring the proportion of the needle-shaped compound X1 in any 10 needle-shaped compounds X is repeated 10 times, but the maximum value of the proportion (content) of these 10 is set to R1, and the minimum value of the proportion (content) is set to R2. Furthermore, the ratio of R1 to R2 (R1 / R2) is taken as the dispersion degree of the needle-shaped compound X1. In this embodiment, by dispersing the needle-shaped compound X1 in the film in such a way that R1 / R2 becomes less than 2.0, the heating rate of the aluminum-plated steel sheet for hot stamping can be further increased. If R1 / R2 exceeds 2.0, the absorption of radiant heat is uneven, so there is a concern that the effect of increasing the heating rate will also be uneven. Therefore, R1 / R2 is preferably set to less than 2.0. R1 / R2 may also be set to 2.5 or less or 2.3 or less, or 1.8 or less or 1.6 or less. It should be noted that R1 / R2 is affected by the time to reach 60°C during drying after coating in the manufacturing method of this embodiment. Specifically, by adjusting the arrival time to 10.0 seconds or less, R1 / R2 can be controlled within the above range. According to the definition of R1 / R2, the lower limit of R1 / R2 is 1.0.

[0088] [Composition of Needle-Shaped Compound X1]

[0089] The needle-shaped compound X1 contained in the surface treatment film 13 is preferably graphite. When the surface treatment film 13 contains graphite, the film component decreases after heating during hot stamping, and the performance after hot stamping, such as adhesion after painting, can be maintained.

[0090] In the case of graphite, since it has few functional groups, it takes a long time for decomposition to occur. On the other hand, carbon black, which is a similar carbon-based compound, has a relatively large number of functional groups and thus has the characteristic of being easily decomposed and oxidized at an early stage.

[0091] By setting the content of graphite in the surface treatment film 13 to 5.0 volume % or more, the emissivity of the aluminum-plated steel sheet can be increased, and the heating rate can be accelerated. The content of graphite in the surface treatment film 13 is more preferably 8.0 volume % or more. By setting the content of graphite in the surface treatment film 13 to 8.0 volume % or more, the heating rate can be further accelerated.

[0092] Here, the "graphite" in the present embodiment refers to a compound having a carbon concentration (C concentration) of 85 mass % or more.

[0093] On the other hand, by setting the content of graphite in the surface treatment film 13 to 40.0 volume % or less, the effect of improving the emissivity can be fully obtained, and the increase in the film cost can be suppressed. The content of graphite in the surface treatment film is preferably 30.0 volume % or less. By setting the content of graphite in the surface treatment film 13 to 30.0 volume % or less, the film cost can be further suppressed.

[0094] The content of graphite can be determined by the same method as the content R of the needle-shaped compound X1 described above, except that the C concentration is limited to 85% or more when measuring the ratio (content) of the needle-shaped compound X1 in the needle-shaped compound X.

[0095] <<Binder component (resin)>>

[0096] The content of the binder component that can be contained in the surface treatment film 13 of the present embodiment is preferably 40% by volume or more relative to the total volume of the surface treatment film 13 in terms of ensuring film adhesion.

[0097] As the binder component, various known resins can be used.

[0098] Resin is not particularly limited. For example, polyurethane resin, polyester resin, acrylic resin, epoxy resin, fluororesin, polyamide resin, polyolefin resin, polymer compound obtained by hydrolysis / polycondensation of silane coupling agent can be listed. As resin, resin obtained by crosslinking these resins by butylated melamine resin, methylated melamine resin, butyl methyl mixed melamine resin, urea resin, isocyanate resin or the crosslinking agent component of these mixed systems can also be listed. In addition, electron beam curing type resin, ultraviolet curing type resin etc. can also be listed. Among them, as binder resin, preferably any one or more of polyester resin, epoxy resin, acrylic resin, and carbamate resin. These binder resins can be used alone, or two or more can be mixed and used.

[0099] It should be noted that, for example, when a polyurethane resin is used as an adhesive component, the polyurethane resin is preferably a polyether-based polyurethane resin. This is because, compared with a polyester-based polyurethane resin, the use of a polyether-based polyurethane resin can prevent the occurrence of hydrolysis caused by acid or alkali, because, compared with a polycarbonate-based polyurethane resin, the formation of a hard and brittle film can be suppressed, thereby ensuring the adhesion during processing and the corrosion resistance of the processed portion.

[0100] Whether the polyurethane resin is contained can be determined based on whether a 3330 cm-1 infrared absorption spectrum is observed. -1 (NH telescopic), 1730cm -1(C=O stretch), 1530cm -1 (CN), 1250cm -1 The content of the polyurethane resin can also be determined by using a sample with a known content in advance to prepare a calibration curve showing the relationship between the content and the intensity of the characteristic absorption, and then determining the content from the obtained characteristic absorption intensity.

[0101] In addition, the presence and content of resins other than the above-mentioned polyurethane resin can be determined in the same manner as the above-mentioned polyurethane resin by focusing on the characteristic absorption derived from the functional groups unique to each resin.

[0102] As a component of the treatment liquid for dispersing or dissolving the resin, water or a solvent can be used.

[0103] <<Additives>>

[0104] The surface treatment film 13 of the present embodiment may contain various additives such as a leveling agent, a water-soluble solvent, a metal stabilizer, a corrosion inhibitor, etc. as additives in preparing the treatment liquid before film formation, within a range not impairing the effects of the present invention.

[0105] As the leveling agent, examples of nonionic or cationic surfactants include polyethylene oxide or polypropylene oxide adducts and acetylene glycol compounds.

[0106] Examples of the water-soluble solvent include alcohols such as ethanol, isopropanol, tert-butyl alcohol and propylene glycol, cellosolves such as ethylene glycol monobutyl ether and ethylene glycol monoethyl ether, esters such as ethyl acetate and butyl acetate, and ketones such as acetone, methyl ethyl ketone and methyl isobutyl ketone.

[0107] Examples of the metal stabilizer include chelate compounds such as EDTA (ethylenediaminetetraacetic acid) and DTPA (diethylenetriaminepentaacetic acid).

[0108] Examples of the corrosion inhibitor include amine compounds such as ethylenediamine, triethylenepentamine, guanidine, and pyrimidine.

[0109] In addition, the content of the above-mentioned binder component or additive can also be measured in the same manner as in the case of the needle-shaped compound.

[0110] <<Silicon Dioxide>>

[0111] As mentioned above, the surface treatment film 13 of the present embodiment may not contain silicon dioxide, or may contain silicon dioxide within a certain range. More specifically, in the surface treatment film 13 of the present embodiment, the content of silicon dioxide may be 0 to 0.3 g / m 2. In the case of more than 0.3g / m 2 When silicon dioxide is contained, the temperature rise effect cannot be expected, and on the other hand, the cost is high, so it is not preferred in terms of economic efficiency. In addition, silicon dioxide is a substance with low conductivity, so when it exceeds 0.3 g / m 2 However, when silicon dioxide is contained, it is not preferable in terms of weldability after hot stamping. When silicon dioxide is contained, the content of silicon dioxide in the surface treatment film 13 is as small as possible. The content of silicon dioxide in the surface treatment film is more preferably 0.10 g / m 2 Below, more preferably 0.05 g / m 2 the following.

[0112] <<Thickness of surface treatment film>>

[0113] The average film thickness of the surface treatment film 13 containing the above-mentioned components is preferably set to 0.5 to 15.0 μm, for example. If the average film thickness of the surface treatment film 13 is less than 0.5 μm, the heating rate during hot stamping cannot be fully increased. On the other hand, if the average film thickness of the surface treatment film 13 exceeds 15.0 μm, the effect of accelerating the heating rate during hot stamping is saturated, and in contrast, the production cost becomes high, so it is economically disadvantageous. In addition, if the film thickness of the surface treatment film 13 is to be thickened, the productivity is reduced because time is required for the formation of the surface treatment film 13 and the drying after the application of the treatment agent. By setting the film thickness of the surface treatment film 13 within the above-mentioned range, the heating rate can be increased. The average film thickness of the surface treatment film is more preferably greater than 1.0 μm or greater than 2.0 μm, and less than 12 μm, less than 10 μm, or less than 7.0 μm.

[0114] <Base treatment film>

[0115] In order to improve the adhesion of the surface treatment film 13 , a base treatment film 14 (chemical conversion treatment layer) may be provided between the surface treatment film 13 and the aluminum plating layer 12 .

[0116] The base treatment film 14 may also include any one or more selected from resin, silane coupling agent, zirconium compound, silicon dioxide, phosphoric acid and its salt, fluoride, and vanadium compound. If these substances are included, the film-forming property of the chemical conversion treatment agent used for the base treatment film 14 after coating, the barrier property (density) of the film to corrosion factors such as moisture and corrosive ions, and the film adhesion to the plated surface are further improved, which helps to improve the corrosion resistance of the film. In particular, if the base treatment film 14 includes any one or more of a silane coupling agent and a zirconium compound, a cross-linked structure is formed in the film, and the bonding with the plated surface is also strengthened, so that the adhesion and barrier property of the film can be improved.

[0117] Furthermore, if the base treatment film 14 contains one or more of silicon dioxide, phosphoric acid and its salts, fluorides, and vanadium compounds, it can improve corrosion resistance by forming a precipitated film or a passivation film on the plated surface or the base steel sheet surface as an inhibitor.

[0118] [Amount of base treatment film applied to each side of the coating]

[0119] The amount of the base treatment film 14 deposited on one surface of the plated layer is preferably 10 to 1000 mg / m2 in terms of solid content. 2 . Less than 10mg / m 2 When the concentration exceeds 1000 mg / m 2 , sometimes the processing adhesion is reduced.

[0120] The adhesion amount of the base treatment film 14 per one surface of the plated steel sheet is more preferably 20 to 800 mg / m 2 , more preferably 50 to 600 mg / m 2 .

[0121] <Aluminum coating>

[0122] The aluminum-plated steel sheet 10 for hot stamping of the present embodiment has an aluminum coating 12 in at least one surface of the base steel sheet 11 and in at least a portion between the base steel sheet 11 and the surface treatment film 13. By having the aluminum coating 12, the corrosion resistance after painting after hot stamping can be further improved. In addition, by the presence of the aluminum coating 12, the generation of iron oxide scale by heating during hot stamping can be prevented. Iron oxide scale becomes a burden on manufacturing because it contaminates the heating furnace or adheres to the rollers used for conveying. Therefore, when iron oxide scale is generated, in order to remove the iron oxide scale, processes such as shot peening become necessary, which is not economically preferred.

[0123] <Base Steel Plate>

[0124] Next, the base steel plate 11 of the hot stamping aluminum-plated steel plate 10 of the present embodiment is described. The base steel plate 11 is not particularly limited as long as it can be suitably used in the hot stamping method. As a steel plate that can be applied to the hot stamping aluminum-plated steel plate of the present embodiment, for example, the following steel plates can be exemplified: the chemical composition of which is calculated by mass % as follows:

[0125] C: 0.03~0.60%,

[0126] Si: 0.01-0.60%,

[0127] Mn: 0.50~3.00%,

[0128] P: 0.050% or less,

[0129] S: 0.020% or less,

[0130] Al: 0.100% or less,

[0131] Ti: 0.01-0.10%,

[0132] B: 0.0001~0.0100%,

[0133] N: 0.010% or less,

[0134] Cr: 0~1.00%,

[0135] Ni: 0-2.00%,

[0136] Cu: 0~1.000%,

[0137] Mo: 0-1.00%,

[0138] V: 0~1.00%,

[0139] Nb: 0-1.00%,

[0140] Sn: 0~1.00%,

[0141] W: 0~1.00%,

[0142] Ca: 0~0.010%

[0143] REM: 0~0.30%,

[0144] The remainder: Fe and impurities.

[0145] In addition, as the form of the base steel plate 11, for example, a steel plate such as a hot-rolled steel plate or a cold-rolled steel plate can be exemplified. The chemical composition of the base steel plate is described in detail below. It should be noted that in the following description of the chemical composition of the base steel plate 11, the description of "%" means "mass %" unless otherwise specified.

[0146] [C: 0.03~0.60%]

[0147] C is contained in order to ensure the target mechanical strength. When the C content is 0.03% or more, sufficient improvement in mechanical strength can be obtained, and the effect of containing C can be fully obtained.

[0148] Therefore, the C content is preferably 0.03% or more. The C content is more preferably 0.20% or more. On the other hand, by making the C content 0.60% or less, the strength of the steel sheet can be effectively improved, and the reduction in elongation and cross-sectional reduction can be suppressed. Therefore, the C content is preferably 0.60% or less. The C content is more preferably 0.40% or less.

[0149] [Si: 0.01 to 0.60%]

[0150] Si is one of the strength-enhancing elements that improves mechanical strength, and is contained in order to ensure the target mechanical strength, similar to C. When the Si content is 0.01% or more, the strength-enhancing effect can be fully exerted, and a sufficient improvement in mechanical strength can be obtained. Therefore, the Si content is preferably 0.01% or more. The Si content is more preferably 0.10% or more. On the other hand, Si is also an oxidizable element, so when the Si content is 0.60% or less, the decrease in wettability during hot-dip Al plating caused by the influence of Si oxides formed in the surface layer of the steel plate can be suppressed, and the occurrence of unplated coating can be suppressed. Therefore, the Si content is preferably 0.60% or less. The Si content is more preferably 0.40% or less.

[0151] [Mn: 0.50~3.00%]

[0152] Mn is one of the strengthening elements that strengthen steel and is also one of the elements that improve hardenability. Furthermore, Mn is an element that is also effective in preventing hot brittleness caused by S, which is one of the impurities. These effects can be fully obtained by having a Mn content of more than 0.50%. Therefore, in order to reliably show the above effects, the Mn content is preferably more than 0.50%. The Mn content is more preferably more than 0.80%. On the other hand, since Mn is an austenite-forming element, the retained austenite phase does not become too much by having a Mn content of less than 3.00%, which can suppress the reduction in strength. Therefore, the Mn content is preferably less than 3.00%. The Mn content is more preferably less than 1.50%.

[0153] [P: 0.050% or less]

[0154] P is an impurity contained in steel. By setting the P content to 0.050% or less, the P contained in the steel plate can be segregated in the grain boundaries of the steel plate, which can suppress the reduction in the toughness of the base material of the formed body after hot stamping, and the reduction in the delayed fracture resistance of the steel plate can be suppressed. Therefore, the P content is preferably 0.050% or less, and the P content is preferably reduced as much as possible. As needed, the P content can also be set to 0.045% or less or 0.040%. The lower limit of the P content is 0%, but the lower limit can also be set to 0.001% or 0.005%.

[0155] [S: 0.020% or less]

[0156] S is an impurity contained in steel. When the S content is 0.020% or less, it is possible to suppress the S contained in the steel plate from forming sulfides and reducing the toughness of the steel plate, and it is possible to suppress the reduction in delayed fracture resistance of the steel plate. Therefore, the S content is preferably 0.020% or less, and the S content is preferably reduced as much as possible. As required, the S content may be set to 0.015% or less or 0.010% or less. The lower limit of the S content is 0%, but the lower limit may be set to 0.001% or 0.002%.

[0157] [Al: 0.100% or less]

[0158] Al is generally used for the purpose of deoxidation of steel. On the other hand, by making the Al content 0.100% or less, the rise of the Ac3 point of the steel plate can be suppressed, so the heating temperature required to ensure the hardenability of the steel during hot stamping can be reduced, which is preferred in hot stamping manufacturing. Therefore, the Al content of the steel plate is preferably 0.100% or less, more preferably 0.050% or less, and further preferably 0.010% or less.

[0159] [Ti: 0.01~0.10%]

[0160] Ti is one of the strength strengthening elements. When the Ti content is 0.01% or more, the strength improvement effect and the oxidation resistance improvement effect can be fully obtained. Therefore, in order to reliably show the above effects, the Ti content is preferably 0.01% or more. The Ti content is more preferably 0.03% or more. On the other hand, when the Ti content is 0.10% or less, for example, the formation of carbides or nitrides can be suppressed, the softening of steel can be suppressed, and the target mechanical strength can be fully obtained. Therefore, the Ti content is preferably 0.10% or less. The Ti content is more preferably 0.08% or less.

[0161] [B: 0.0001~0.0100%]

[0162] B has the effect of improving strength by acting during quenching. Such a strength improvement effect can be fully obtained by a B content of 0.0001% or less. Therefore, the B content is preferably 0.0001% or more. The B content is more preferably 0.0010% or more. On the other hand, by a B content of 0.0100% or less, the formation of inclusions is reduced and the embrittlement of the steel plate is suppressed, and the reduction in fatigue strength can be suppressed. Therefore, the B content is preferably 0.0100% or less. The B content is more preferably 0.0040% or less.

[0163] [N: 0.010% or less]

[0164] N is an impurity contained in steel. When the N content is 0.010% or less, the formation of nitrides caused by N contained in the steel plate can be suppressed, and the toughness reduction of the steel plate can be suppressed. Furthermore, when B is contained in the steel plate, the bonding of N contained in the steel plate with B can be suppressed to reduce the amount of solid solution B, and the reduction of the hardenability improvement effect of B can be suppressed. Therefore, the N content is preferably 0.010% or less, and the N content is more preferably reduced as much as possible.

[0165] In addition, the base steel sheet of the hot stamping steel sheet of the present embodiment may further contain one or more elements selected from the group consisting of Cr, Mo, Ni, Cu, Mo, V, Nb, Sn, W, Ca and REM as optional elements. The lower limit of the content of these elements is 0%.

[0166] [Cr: 0~1.00%]

[0167] Cr is an element that improves the hardenability of the steel sheet. In order to fully obtain the above effect, it is preferred that the Cr content be set to 0.01% or more. On the other hand, by setting the Cr content to 1.00% or less, the effect can be fully obtained and the cost increase can be suppressed. Therefore, when the Cr content is contained, it is preferably set to 1.00% or less. As required, the Cr content may also be set to 0.70% or less or 0.50% or less.

[0168] [Ni: 0~2.00%]

[0169] Ni is an element that can improve the hardenability of steel and stably ensure the strength of the steel plate component after quenching. In order to fully demonstrate the above effect, it is preferred that the Ni content is set to 0.10% or more. On the other hand, by having a Ni content of 2.00% or less, the above effect is fully obtained, and the economy is improved. Therefore, the Ni content when contained is preferably set to 2.00% or less. As required, the Ni content can also be set to 1.20% or less, 0.80% or less, or 0.50% or less.

[0170] [Cu: 0~1.000%]

[0171] Cu is an element that can improve the hardenability of steel and stably ensure the strength of the steel plate component after quenching. In addition, Cu improves pitting resistance in a corrosive environment. In order to fully demonstrate the above effect, it is preferred that the Cu content is set to 0.100% or more. On the other hand, by having a Cu content of 1.000% or less, the above effect is fully obtained, and the economy is improved. Therefore, the Cu content when contained is preferably set to 1.000% or less. As required, the Cu content can also be set to 0.600% or less, 0.400% or less, or 0.200% or less.

[0172] [Mo: 0-1.00%]

[0173] Mo is an element that can improve the hardenability of steel and stably ensure the strength of the steel plate component after quenching. In order to fully demonstrate the above effect, it is preferred to set the Mo content to 0.10% or more. On the other hand, by setting the Mo content to 1.00% or less, the above effect can be fully obtained, and the economic efficiency is improved. Therefore, when Mo is contained, the Mo content is preferably set to 1.00% or less. As needed, the Mo content can also be set to 0.60% or less, 0.40% or less, or 0.20% or less.

[0174] [V: 0~1.00%]

[0175] V is an element that can improve the hardenability of steel and stably ensure the strength of the steel plate component after quenching. In order to fully demonstrate the above effect, it is preferred that the V content is set to 0.10% or more. On the other hand, by having a V content of 1.00% or less, the above effect is fully obtained, and the economy is improved. Therefore, when V is contained, the V content is preferably set to 1.00% or less. As required, the V content can also be set to 0.60% or less, 0.40% or less, or 0.20% or less.

[0176] [Nb: 0~1.00%]

[0177] Nb is an element that can improve the hardenability of steel and stably ensure the strength of the steel plate component after quenching. In order to fully demonstrate the above effect, it is preferred to set the Nb content to 0.01% or more. On the other hand, by setting the Nb content to 1.00% or less, the above effect can be fully obtained, and the economic efficiency is improved. Therefore, when Nb is contained, the Nb content is preferably set to 1.00% or less. As needed, the Nb content can also be set to 0.50% or less, 0.20% or less, or 0.10% or less.

[0178] [Sn: 0~1.00%]

[0179] Sn is an element that improves pitting resistance in a corrosive environment. In order to fully demonstrate the above effect, the Sn content is preferably set to 0.01% or more. On the other hand, by setting the Sn content to 1.00% or less, the reduction in grain boundary strength can be suppressed, and the reduction in toughness can be suppressed. Therefore, the Sn content when contained is preferably set to 1.00% or less. As required, the Sn content can also be set to 0.40% or less, 0.10% or less, or 0.05% or less.

[0180] [W: 0~1.00%]

[0181] W is an element that can improve the hardenability of steel and stably ensure the strength of steel plate components after quenching. In addition, W improves pitting resistance in a corrosive environment. In order to fully demonstrate the above effect, it is preferred to set the W content to 0.01% or more. On the other hand, by setting the W content to 1.00% or less, the above effect is fully obtained, and the economic efficiency is improved. Therefore, when the W content is contained, it is preferably set to 1.00% or less. As required, the W content can also be set to 0.60% or less, 0.40% or less, or 0.20% or less.

[0182] [Ca: 0~0.010%]

[0183] Ca is an element that has the effect of miniaturizing inclusions in steel and improving toughness and ductility after quenching. In order to fully demonstrate the above effect, it is preferred that the Ca content is set to 0.001% or more, and more preferably to 0.002% or more. On the other hand, by having a Ca content of 0.010% or less, its effect can be fully obtained and the cost can be suppressed. Therefore, when contained, the Ca content is preferably set to 0.010% or less, and more preferably to 0.004% or less. As required, the Ca content can also be set to 0.008% or less, 0.006% or less, or 0.0004% or less.

[0184] [REM: 0~0.30%]

[0185] REM, like Ca, is an element that has the effect of miniaturizing inclusions in steel and improving toughness and ductility after quenching. In order to fully demonstrate the above effect, it is preferred to set the REM content to 0.001% or more, and more preferably to 0.002% or more. On the other hand, by setting the REM content to 0.30% or less, its effect can be fully obtained and the cost can be suppressed. Therefore, when contained, the REM content is preferably set to 0.30% or less, and more preferably to 0.20% or less. As needed, the Ca content can also be set to 0.10% or less, 0.05% or less, or 0.02% or less.

[0186] Here, REM refers to Sc, Y and lanthanoid elements, a total of 17 elements, and the above REM content refers to the total content of these elements. REM is added to molten steel using, for example, Fe-Si-REM alloy, and the alloy contains, for example, Ce, La, Nd, and Pr.

[0187] The remainder other than the above components is Fe and impurities. In addition to the above components, the base steel plate 11 may also contain impurities mixed in the manufacturing process, etc. within a range that does not hinder the effect of the present invention. Examples of the impurities include Zn (zinc) and Co (cobalt).

[0188] The portion of the surface of the plated steel sheet including the base steel sheet 11 having the above-mentioned chemical composition and the aluminum plating layer 12 to which the surface treatment film 13 is applied can be heated and quenched by hot stamping to produce, for example, a hot stamping component having a tensile strength of about 1000 MPa or more. In addition, in the hot stamping method, since the pressing process can be performed in a softened state at a high temperature, it can be easily formed.

[0189] (Method for producing aluminum-plated steel sheet for hot stamping)

[0190] An example of a method for manufacturing an aluminum-plated steel sheet for hot stamping according to the present embodiment is described below. It should be noted that the manufacturing method is not particularly limited as long as the aluminum-plated steel sheet for hot stamping according to the present embodiment has the above-mentioned structure. The following manufacturing method is an example for manufacturing an aluminum-plated steel sheet for hot stamping according to the present embodiment, and is a preferred example of a method for manufacturing an aluminum-plated steel sheet for hot stamping according to the present embodiment.

[0191] <Base Steel Plate>

[0192] The base steel sheet for aluminum plating is not particularly limited as long as it can be suitably used in the hot stamping method. Examples of the form of the base steel sheet include steel sheets such as hot-rolled steel sheets and cold-rolled steel sheets.

[0193] <Aluminum coating>

[0194] The aluminum-plated steel sheet for hot stamping of the present embodiment preferably has an aluminum coating in at least a portion between the base steel sheet and the surface treatment film on one or both sides of the base steel sheet. By having an aluminum coating, the corrosion resistance after painting after hot stamping can be further improved. In addition, by the presence of the aluminum coating, the formation of iron oxide scale by heating during hot stamping can be prevented. The iron oxide scale becomes a burden on manufacturing because it contaminates the heating furnace or adheres to the rollers used for conveying. Therefore, when iron oxide scale is generated, in order to remove the iron oxide scale, processes such as shot peening become necessary, which is not economically preferred.

[0195] The type of the aluminum plating layer is not particularly limited. The composition constituting the aluminum plating layer includes aluminum plating, Al-Si plating, Al-Si-Mg plating, Al-Si-Ca plating, and the like.

[0196] For example, the chemical composition (average chemical composition) of the aluminum plating layer may be a plating layer containing, in mass%, Al: 85.0-95.0%, Si: 2.0-15.0%, Fe: 1-15.0%, Cr: 0% or more and less than 1.0%, Mo: 0% or more and less than 1.0%, Zn: 0% or more and less than 1.0%, V: 0% or more and less than 1.0%, Ti: 0% or more and less than 1.0%, Sn: 0% or more and less than 1.0%, Ni: 0% or more and less than 1.0%, Cu: 0% or more and less than 1.0%, W: 0% or more and less than 1.0%, Bi: 0% or more and less than 1.0%, Mg: 0% or more and less than 1.0%, Ca: 0% or more and less than 1.0%, with the remainder being impurities.

[0197] If the Al content in the aluminum plating layer is less than 85.0%, the corrosion resistance after hot stamping (corrosion resistance in the hot stamping formed body) deteriorates. Therefore, the Al content is preferably 85.0% or more. The Al content is more preferably 88.0% or more. On the other hand, if the Al content in the aluminum plating layer exceeds 95.0%, the coating adhesion sometimes deteriorates. Therefore, the Al content is preferably set to 95.0% or less. The Al content is more preferably 92.0% or less.

[0198] If the Si content in the aluminum plating layer is less than 2.0%, the coating adhesion sometimes deteriorates. Therefore, the Si content is preferably set to 2.0% or more. The Si content is more preferably 3.0% or more, and further preferably 4.0% or more. On the other hand, if the Si content in the aluminum plating layer exceeds 15.0%, the coating adhesion sometimes deteriorates. Therefore, the Si content is preferably set to 15.0% or less. The Si content is more preferably 13.0% or less.

[0199] The Fe content is preferably 1.0% or more and 15.0% or less.

[0200] The chemical composition of the aluminum plating layer can be measured by the fluorescent X-ray method in accordance with JIS K 0119: 2008. That is, using a sample with a known content of the target element, the relationship between the X-ray intensity and the content is determined in advance. Based on the calibration curve prepared based on it, the content of each element of the unknown sample, that is, the chemical composition, can be determined.

[0201] The coating weight is preferably 10 g / m 2 ~120g / m 2 . Below 10g / m 2 If the thickness exceeds 120 g / m, there may be defects in the coating and iron scale may be generated during hot stamping. 2 , the cost becomes high and uneconomical. Preferably 30g / m 2 ~100g / m 2 .

[0202] In addition, examples of the method for forming the aluminum plating layer include hot-dip plating, electroplating, physical vapor deposition, and chemical vapor deposition, but are not particularly limited.

[0203] <Surface treatment film>

[0204] The method for producing the surface treatment film is not particularly limited, and examples thereof include a method in which the film-forming components are mixed, stirred with a disperser, and the dissolved or dispersed surface treatment agent is applied to the plated layer and then dried.

[0205] As the raw material of the needle-shaped compound contained in the surface treatment film layer, the compound with hexagonal crystal structure having a ratio of major diameter to minor diameter of more than 4 and less than 50 is used. As the compound with hexagonal crystal structure, there are lanthanum silicate, magnesium diboride, beryllium oxide, zinc oxide, graphite (C), β-quartz, nickel ore (NiS), wurtzite (ZnS) etc. Among them, it is preferred to use graphite (C) with a carbon concentration of 90 mass %. The surface treatment film is manufactured using a surface treatment agent obtained by dispersing these raw materials in a solvent (such as water or a solvent). It should be noted that, in the case where the ratio of the major diameter of the compound used to the minor diameter is unclear, as required, it is also possible to confirm by preliminary tests etc. the surface treatment film of the needle-shaped compound including the ratio of the required major diameter to the minor diameter.

[0206] In order to set the proportion of the needle-shaped compound X1 having a minor diameter of 20 nm or more, a major diameter / minor diameter ratio of 4 to 50, and a hexagonal crystal structure to 70% or more in terms of number %, and to set the proportion of the needle-shaped compound X2 having the angle α of 0 degree or more and 40 degrees or less in the needle-shaped compound X1 to 70% or more in terms of number %, it is effective to continuously stir a solution obtained by adjusting the pH to 11.0 or more with an aqueous sodium hydroxide solution or ammonium water at a liquid temperature of 30 to 50° C. for 1 to 7 days. That is, by using a compound having a hexagonal crystal structure as a raw material of the needle-shaped compound and controlling the pH of the treatment agent and the stirring conditions to an appropriate range, the proportion of the needle-shaped compound X1 having a major diameter / minor diameter ratio of 4 to 50 and the proportion of the needle-shaped compound X2 having an angle α of 0 degree or more and 40 degrees or less can be sufficiently increased (for example, 70% or more in terms of number %).

[0207] When using a treatment liquid obtained by dispersing a raw material in water or a solvent (such as acetone), the treatment liquid is applied to a substrate such as a steel plate to which a coating layer has been previously applied, and after the water or solvent is fully dried, TEM observation is performed to confirm in advance that the short diameter is 20 nm or more and the ratio of the long diameter to the short diameter is 4 to 50. By using the raw materials and manufacturing methods selected in this way, a surface treatment film mixed with a binder component can be obtained.

[0208] Furthermore, in the surface treatment film, in order to increase the proportion of the needle-shaped compound X2 whose smaller angle α is 0 degrees or more and 40 degrees or less among the angles at the intersection of the straight line parallel to the long diameter and the straight line parallel to the coating surface in the needle-shaped compound X1, it is effective to add 40 to 70 g of the treatment liquid to a container with a stirring rod and stir it at 80 to 120 rpm before applying the treatment liquid obtained by dispersing the raw materials in water or a solvent within 5.0 seconds. It should be noted that, as described above, the treatment liquid adjusted to a pH of 11.0 or more can also be applied while stirring in a container that has been stirred for more than 1 day.

[0209] It is also effective to set the viscosity of the treatment liquid to 3.0 to 10.0 mPa·s and the surface tension to 20 to 60 mN / m. Furthermore, it is also effective to set the time for the steel sheet to reach 60° C. to 3.0 seconds or more during heating and drying after applying the treatment liquid.

[0210] The method for producing the surface treatment agent is not particularly limited, and for example, a method of mixing the various film-forming components and stirring them with a disperser to dissolve or disperse them can be cited. In order to improve the solubility or dispersibility of the various film-forming components, a known hydrophilic solvent or the like may be added as needed. In the chemical conversion treatment agent for the substrate treatment film 14, an acid or a base for adjusting the pH may also be added within a range that does not impair its performance.

[0211] In order to form a surface treatment film layer, a surface treatment agent is applied to the plated steel plate, and the coating film is heated and dried. The coating method of the chemical conversion treatment agent is not particularly limited, and can be a generally known coating method, such as a method using roller coating, air spraying, airless spraying, dipping, etc. The heating and drying temperature is preferably 50 to 250°C. When it is lower than 50°C, the evaporation rate of water is slow, and sufficient film-forming properties cannot be obtained, so the rust prevention power is sometimes insufficient. If it exceeds 250°C, the alkyl part of the silane coupling agent as an organic substance is modified due to thermal decomposition, etc., and sometimes the adhesion and corrosion resistance are reduced. The heating temperature is more preferably 70 to 160°C.

[0212] The heat drying method is not particularly limited, and examples thereof include methods using hot air, induction heating, near infrared rays, direct flame, etc., alone or in combination.

[0213] (Method for manufacturing hot stamped component)

[0214] Various hot stamping parts such as those exemplified in the automobile frame parts can be produced using an aluminum-plated steel sheet for hot stamping to which the above-mentioned surface treatment film is applied to the entire surface of at least one surface.

[0215] First, a surface treatment film is applied to the entire surface of at least one surface of a metal raw material such as a coiled steel plate. Then, various processes such as punching by cutting or pressing are performed to obtain the aluminum-plated steel plate for hot stamping of the present embodiment. In addition, the aluminum-plated steel plate for hot stamping of the present embodiment can also be obtained by applying a surface treatment film to a steel plate that has been punched by cutting or pressing. In addition, by partially reducing the film thickness of the surface treatment film, for example, in the application of welding a plurality of steel plates before hot stamping, it becomes easy to conduct electricity, and the spot weldability can be improved.

[0216] For example, a hot stamping steel plate to which a surface treatment film is applied as described above is subjected to hot stamping. As a heating device, for example, there is an electric heating furnace, a gas heating furnace, or a conventional heating device equipped with a far-infrared furnace, an infrared heater, etc. The surface on one side to which the emissivity is increased by applying a surface treatment film has a large heat transfer effect caused by radiation, so the heating rate is fast. Therefore, the temperature is rapidly raised to a temperature above the Ac3 point at which the metal structure is transformed into an austenite phase. Therefore, in the manufacturing method of the hot stamping component of the present embodiment, the productivity of the hot stamping component can be further improved by seeking to shorten the heating time. In the present embodiment, there is no particular limitation on the specific heating conditions, as long as the heating device used is appropriately controlled.

[0217] Next, the heated steel sheet is formed and cooled. The portion heated to a temperature above the Ac3 point, at which the metal structure of the steel material is transformed into an austenite phase, is quenched and its strength is increased. Thus, a hot stamping component with increased strength through quenching can be obtained.

[0218] Example

[0219] The following describes an embodiment of the present invention, but the conditions in the embodiment are only a condition example adopted to confirm the feasibility and effect of the present invention, and the present invention is not limited to this condition example. As long as it does not deviate from the gist of the present invention and achieves the purpose of the present invention, the present invention can adopt various conditions.

[0220] As the base steel plate, it is preferred to use a steel plate having high mechanical strength (referring to various properties related to mechanical deformation and fracture, such as tensile strength, yield point, elongation, cross-sectional reduction, hardness, impact value, fatigue strength, etc.). The chemical composition of the base steel plate before plating used in the hot stamping steel plate shown in the following examples is shown in the following Table 1.

[0221]

[0222] A surface treatment film was applied to the base steel plates (steel No. S1 to S10) having the chemical composition shown in Table 1. More specifically, for each base steel plate, a steel plate with a width of 100 mm × a length of 200 mm and a thickness of 1.6 mm was prepared, and after hot-dip plating with an Al-10% Si plating bath, a surface treatment film was applied to the entire surface of both sides. Here, the record "-" in Table 1 means that the corresponding element content is 0% in the significant figures (the value to the minimum digit) specified in this embodiment.

[0223] The manufacturing method of the treatment liquid is set to the conditions shown in Table 2. That is, lanthanum silicate, magnesium diboride, beryllium oxide, zinc oxide, β-quartz, graphite, zirconium oxide powder or dispersion is used as a solute in water or a solvent, and after being aged at a specified pH, temperature, and stirring time, it is applied to an aluminum-plated steel plate by a roll coater. When drying in a hot air furnace, the time to reach 60°C is controlled by the wind speed and the temperature in the furnace. It should be noted that in manufacturing No. A9, acetone is used as an additive in the treatment liquid.

[0224] In addition, in manufacturing No. A14 to A16 (corresponding to symbols B14 to B16 in Table 3), a surface treatment film was applied to the surface of the Al-10% Si plated steel sheet by applying a solution in which a binder component was dispersed using a roll coater and drying. In manufacturing No. A14, an aqueous treatment liquid containing a SiO2 compound was added as a binder component, in manufacturing No. A15, a solution in which an acrylic resin was dispersed was used, and in manufacturing No. A16, a solution in which a polyurethane resin was dispersed was used.

[0225] The film thickness of the surface treatment film is set to be within the range of 1.0 to 10 μm.

[0226] Here, the underlined parts in Table 2 indicate conditions outside the range of the preferred production conditions of the present embodiment.

[0227]

[0228] After that, a thermocouple is connected to the center of the steel plate with the surface treatment film so that the temperature of each position can be measured. Then, the steel plate is heated in an electric heating furnace set at 920°C, and when the steel plate with the film reaches 910°C, the steel plate is taken out of the heating furnace. The steel plate is quickly cooled with a flat die to obtain a hot stamping component.

[0229] The temperature rise rate of the portion to which the surface treatment film was applied and the adhesion of the surface treatment film were investigated.

[0230] The evaluation method of each evaluation item is set as follows.

[0231] (1) Heating rate (heating characteristics)

[0232] The temperature rise rate in each steel plate was calculated and evaluated based on the temperature change obtained by the thermocouples installed on each steel plate and the heating time in the electric heating furnace. Specifically, the average temperature rise rate from room temperature to 910°C was calculated and evaluated based on the following evaluation criteria, and a score of "2" or above was set as passing.

[0233] (score)

[0234] 5: Heating rate is above 5.0℃ / s

[0235] 4: Heating rate is 4.5℃ / s or more and less than 5.0℃ / s

[0236] 3: The heating rate is above 4.0℃ / s and below 4.5℃ / s

[0237] 2: The heating rate is 3.5℃ / s or more and less than 4.0℃ / s

[0238] 1: The heating rate is above 2.0℃ / s and below 3.5℃ / s

[0239] (2) Adhesion of surface treatment film

[0240] The hot stamped parts were subjected to phosphoric acid chemical conversion treatment and 15 μm thick electrodeposition coating, and baked at 170°C for 20 minutes to impart a surface treatment film. After that, the parts were immersed in deionized water at 60°C for 250 hours, and the peeling state of the surface treatment film was confirmed. A score of "2" was set as acceptable.

[0241] (score)

[0242] 2: Excellent (no peeling)

[0243] 1: Good (less than 3% peeling in terms of area ratio)

[0244] The evaluation results obtained above are shown in Table 3. In addition, the "carbon concentration of the needle-shaped compound" shown in Table 3 is the average value (unit: mass %) of the carbon concentration of the needle-shaped compound X2 analyzed by EDS.

[0245]

[0246] B1 to B19 are invention examples, and b1 to b12 are comparative examples. The particle size of the needle-shaped compounds is 20 nm to 400 nm.

[0247] In Inventive Examples B1 to B19, the ratio (number %) of the needle-shaped compound X1 having a hexagonal crystal structure and a major axis / minor axis ratio of 4 to 50 to all needle-shaped compounds (including needle-shaped compounds having a ratio of less than 4 and more than 50) is 70% or more, and the ratio (number %) of the needle-shaped compound X2 having an angle α of 0 to 40 degrees with the surface of the surface-treated film among the needle-shaped compounds X1 is 70% or more. The rating of their heating rate (heating characteristics) is 2 or more.

[0248] On the other hand, in Comparative Example b1, the compound used was not suitable, and the proportion (number %) of the needle-shaped compound X1 having a hexagonal crystal structure with a major axis / minor axis ratio of 4 to 50 was less than 70%. In addition, in Comparative Example b2, the compound used was not suitable, and the crystal structure was not hexagonal. The compound used in Comparative Example b3 was not suitable, and the proportion (number %) of the needle-shaped compound X2 was less than 70%.

[0249] The compound used in Comparative Example b4 is carbon black, and the compound used is inappropriate. In Comparative Examples b5 and b8, the proportion of needle-shaped compound X1 (number %) and the proportion of needle-shaped compound X2 (number %) are less than 70%. In Comparative Examples b6, b7, b9, and b10 to b12, at least the compound used is inappropriate, and the ratio of the major axis / minor axis of the needle-shaped compound X1 is out of the range of 4 to 50. As a result, the proportion of the needle-shaped compound X1 or the proportion of the needle-shaped compound X2 in Comparative Examples b1 to b12 is low, and the score of the heating rate is 1.

[0250] It should be noted that, in invention examples B7 to B12, except for the proportion (number %) of the needle-shaped compound X1 with a hexagonal crystal structure and a major axis / minor axis ratio of 4 to 50, the crystal structure, the angle α with the surface, and the content R of 2 to 60%, the score of the heating rate was improved to 3.

[0251] In B13 in which the carbon concentration of the needle-shaped compound X1 was 90 mass %, the heating rate was higher than that of B12. Inventive Examples B12 to B16 in which graphite was used, the scores of the heating rate were further higher than those in the case other than graphite.

[0252] In Invention Examples B14 to B16 containing a resin, the rating of film adhesion was improved from 1 to 2.

[0253] Inventive Example B11 has a better temperature rise characteristic than Inventive Example B17 because the dispersion degree of the needle-shaped compound X1 is good.

[0254] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited to the examples described above. Obviously, a person with ordinary knowledge in the technical field to which the present disclosure belongs can think of various variations or modifications within the scope of the technical ideas recorded in the claims, and understand that these also belong to the technical scope of the present disclosure.

[0255] Industrial Applicability

[0256] According to the above aspect of the present invention, it is possible to provide an aluminum-plated steel sheet for hot stamping that can further improve the productivity of hot stamped parts, and thus the industrial applicability is high.

[0257] Explanation of symbols

[0258] 10 Aluminum-coated steel sheet for hot stamping

[0259] 11. Base steel plate

[0260] 12 Aluminum coating

[0261] 13 Surface treatment film

[0262] 14 Base treatment film

[0263] 15 membrane

Claims

1. An aluminum-plated steel sheet for hot stamping, characterized in that: It has: Base steel plate, an aluminum plating layer provided on at least one surface of the base steel plate, and A surface treatment film is provided on the aluminum plating layer, The surface treatment film contains a needle-shaped compound X, In the needle-shaped compound X, the ratio of the major diameter to the minor diameter is 4 or more and 50 or less, and the proportion of the needle-shaped compound X1 having a hexagonal crystal structure is 70% or more in terms of number %, Among the needle-shaped compounds X1, the proportion of needle-shaped compounds X2 in which the smallest angle formed between a straight line parallel to the major axis and the surface of the aluminum plating layer is 0 degrees or more and 40 degrees or less is 70% or more in terms of number %.

2. The aluminum-plated steel sheet for hot stamping according to claim 1, characterized in that: The content R of the needle-shaped compound X1 is 2% or more and 60% or less in volume %.

3. The aluminum-plated steel sheet for hot stamping according to claim 1 or 2, characterized in that: The carbon concentration of the needle-shaped compound X1 is 90 mass % or more.

4. The aluminum-plated steel sheet for hot stamping according to any one of claims 1 to 3, characterized in that When the content R of the needle-shaped compound X1 is measured at 10 locations and the maximum content is set as R1 and the minimum content is set as R2, the ratio R1 / R2 of R1 to R2 is 2.0 or less.

5. The aluminum-plated steel sheet for hot stamping according to any one of claims 1 to 4, characterized in that The needle-shaped compound X1 is graphite.

6. The aluminum-plated steel sheet for hot stamping according to any one of claims 1 to 5, characterized in that The surface treatment film contains a resin.

Citation Information

Patent Citations

  • Hot press formed product with high corrosion resistance

    JP2003126921A

  • Al PLATED STEEL SHEET FOR HOT PRESS HAVING EXCELLENT TEMPERATURE RISING PROPERTY, AND METHOD FOR PRODUCING THE SAME

    JP2011149084A

  • Method for manufacturing press hardened and coated steel parts at high production rates

    JP2017518438A

  • Machine phenomenon evaluation support device

    JP2022113179A